Reconstructing the Meaning of Terrorism in Political Communication: Ideology and Legitimation Strategies of Islamic Political Parties - Atjih Sukaesih; Yantos; Yudhi Martha Nugraha (International Journal of Science and Society, 2026)
This study investigates how elite actors within Islamic political parties in Indonesia construct and articulate the meaning of terrorism in relation to ideology and electoral strategy. Employing a qualitative constructivist approach, the research draws on semi-structured interviews and party documents to explore the production of political narratives. The findings reveal two dominant tendencies. Moderate Islamic parties define terrorism as individual criminal behavior detached from religious identity and emphasize constitutional commitment and national stability. In contrast, conservative Islamic parties interpret terrorism within broader structural injustices and socio-political dynamics, while still rejecting violence as a legitimate political method. These differing constructions shape framing strategies, deradicalization approaches, and political positioning in democratic competition. The study highlights that terrorism operates not only as a security issue but also as a strategic instrument for political legitimacy and identity differentiation.